Spatial Analysis of Micro Regional Disparities in Level of Development: A Case Study of Saharsa District, Bihar - Mishra, Nitin Kumar; Singh, M. B. (National Geographical Journal of India, 2022)
The process of development is initiated with a change in the economic activities or structure of economy. The socio-economic change does not occur uniformly in different areas. This leads to regional disparities that are caused by a number of factors such as resources, infrastructures, services, skills, capital, government policies etc. On account of regional disparities several economic, social and structural problems take place in concerned area which needs launching of corrective policy measures. The present paper aims to analyse the imbalances in the level of development with spatial emphasis on the regional dimension. In order to analyze the regional disparities of ten blocks of the Saharsa district, twenty four variables have been selected and by using the Development Index (Z-Score Method) regional disparities have been assessed. In the analysis it has been found that Patarghat block attained the top position in overall development while the blocks namely Mahishi and Salkhua gained low level of development.